A Supraparticle-Based Five-Level-Identification Tag That Switches Information Upon Readout - Miller, Franziska; Wintzheimer, Susanne; Prieschl, Johannes; Strauss, Volker; Mandel, Karl (Advanced Optical Materials, 2020)
Product identification tags are of great importance in a globalized world with increasingly complex trading routes and networks. Beyond currently used coding strategies, such as QR codes, higher data density, flexible application as well as miniaturization and readout indication are longed for in the next generation of security tags. In this work, micron-sized supraparticles (SPs) with encoded information (ID) are produced that not only exhibit multiple initially covert identification levels but are also irreversibly marked as “read” upon readout. To achieve this, lanthanide doped CaF2 nanoparticles are assembled in various quantity-weighted ratios via spray-drying in presence of a broad-spectrum stealth fluorophore (StFl), yielding covert spectrally encoded ID-SPs. Using these as pigments, QR codes, initially dominated by the green fluorescence of the StFl, could be generated. Upon thermal energy input, these particle-based tags irreversibly switch to an activated state revealing not only multiple luminescent colors but also spectral IDs. This strategy provides the next generation of material-based security tags with a high data density and security level that switch information upon readout and can be, therefore, used as seal of quality.
CRIS-Team Scopus Importer:2020-12-25
Keywords: multilevel luminescence identification; rare earth doped nanoparticles; security tags; stealth fluorophores; supraparticles

Colorful Luminescent Magnetic Supraparticles: Expanding the Applicability, Information Capacity, and Security of Micrometer-Scaled Identification Taggants by Dual-Spectral Encoding - Müssig, Stephan; Reichstein, Jakob; Miller, Franziska; Mandel, Karl (Small, 2022)
(Sub)micrometer-scaled identification (ID) taggants enable direct identification of arbitrary goods, thereby opening up application fields based on the possibility of tracking, tracing, and anti-counterfeiting. Due to their small dimensions, these taggants can equip in principle even the smallest subcomponents or raw materials with information. To achieve the demanded applicability, the mostly used optically encoded ID taggants must be further improved. Here, micrometer-scaled supraparticles with spectrally encoded luminescent and magnetically encoded signal characteristics are reported. They are produced in a readily customizable bottom-up fabrication procedure that enables precise adjustment of luminescent and magnetic properties on multiple hierarchy levels. The incorporation of commonly used magnetic nanoparticles and fluorescent dyes, respectively, into polymer nanocomposite particles, establishes a convenient toolbox of magnetic and luminescent building blocks. The subsequent assembly of selected building blocks in the desired ratios into supraparticles grants for all the flexibility to freely adjust both signal characteristics. The obtained spectrally resolved visible luminescent and invisible magnetic ID signatures are complementary in nature, thus expanding applicability and information security compared to recently reported optical- or magnetic-encoded taggants. Additionally, the introduced ID taggant supraparticles can significantly enhance the coding capacity. Therefore, the introduced supraparticles are considered as next-generation ID taggants.<br
Keywords: identification taggants; luminescent particles; magnetic particle spectroscopy; magnetic particles; nanoparticles; smart additives; supraparticles

Communicating Particles: Identification Taggant and Temperature Recorder in One Single Supraparticle - Reichstein, Jakob; Miller, Franziska; Wintzheimer, Susanne; Mandel, Karl (Advanced Functional Materials, 2021)
“Communicating particles” are reported that combine an identification (ID) taggant and a temperature recorder in one single entity—a micron-scaled supraparticle. The optical information carriers within the hybrid inorganic-organic supraparticles are three different types of luminescent nanoparticles, which can be read-out using single-wavelength excitation. These three nanoparticle types are assembled into a core-satellite structure via a two-step droplet evaporation technique. The core is built-up from Tb3+ and Eu3+-doped nanophosphors, providing an environmentally stable ID that is easily tunable through ratiometric spectral coding. This core is surrounded by organic, dye-doped polymer nanoparticle satellites, acting as thermal-history-recorders of their environment. Exposed to a threshold temperature, the luminescence of the utilized 7-diethylamino-4-methylcoumarin-doped polymer nanoparticles is irreversibly quenched. This “turn-off ” signal response is attributed to conformational changes in the dyes’ excited state and an alteration of their molecular environment, respectively, triggered by the polymer nanoparticles’ glass transition. Thus, the sensitivity of the temperature recorder can be configured over a wide temperature range by varying the dye-hosting polymer. At the same time, the ID of the particle, stemming from its inorganic building blocks, stays unaffected, thus stable against thermal changes. The idea of communicating particles introduces a promising concept for smart additives.
CRIS-Team Scopus Importer:2021-06-25
Keywords: luminescent nanoparticles; ratiometric spectral coding; smart additives; supraparticles; temperature indicators

Core-Satellite Supraparticles to Ballistically Stamp Nanostructures on Surfaces - Oppmann, Maximilian; Miller, Franziska; Thuerauf, Sandra; Groppe, Philipp; Prieschl, Johannes; Stauch, Claudia; Mandel, Karl (ACS Applied Materials and Interfaces, 2018)
Nanostructured surfaces are of great importance in a very wide range of fields. They can be obtained by imprint or deposition techniques. However, these are usually sophisticated to perform. Generally, it is not easy to equip an object/product with a nanostructure after manufacturing. Yet, it would be very beneficial to achieve a modification of an arbitrary surface with a nanostructure of choice at a later stage by an approach that is simple to perform without the need of sophisticated equipment or excessive treatment by physicochemical methods. Herein, such a process is reported, which combines two "old-fashioned" techniques, namely, sandblasting and rubber-stamping, and translates them to the "nanoworld". By creating core-satellite supraparticles via spray-drying, a ballistic core-satellite stamp particle system is obtained, which can be used to easily transfer a wide range of nanoparticles to a great variety of surfaces to equip these with a nanostructure and subsequently advanced properties. These include water-repellant, antifouling, or antidust surfaces. Moreover, it is also demonstrated that the approach can be used to manufacture well-defined nanoimprinted surfaces. Such surfaces showed an improved spreading behavior for aliphatic alcohols, thus making such surfaces, for instance, very susceptible for disinfectants. All in all, the simple technique described herein has a great potential for creating nanostructured surfaces on nearly any surface.
CRIS-Team Scopus Importer:2020-04-02
Keywords: coatings; imprint; nanostructures; sandblasting; supraparticles; surface modification

Hybrid Inorganic–Organic Luminescent Supraparticle Taggants with Switchable Dual-Level ID - Miller, Franziska; Reichstein, Jakob; Mandel, Karl (Advanced Optical Materials, 2022)
Tracking and tracing of objects are of paramount importance for realizing a Circular Economy and can be achieved by incorporating micrometer-scaled luminescent identification (ID) taggants. While established systems are passive, displaying merely an ID feature, for monitoring a products’ life cycle, conscious taggants with stimuli-triggered switchable ID signals, e.g., to record a recycling step, are desired. Herein, micrometer-scaled hybrid inorganic–organic taggants with a temperature-triggered switchable luminescent ID are reported. They are produced by assembling eight different types of organic and inorganic nanoparticles (NPs) via a two-step spray-drying process into supraparticles (SPs) with a core–shell structure. This hierarchical structure and well-balanced mass-ratios of the utilized nanosized building blocks are key to controlling the occurring coupling effects within SPs, thus, to obtain the switchable ID functionality. Initially, the temperature-inert inorganic luminescent ID-level, located in the core, is concealed by a mutable organic ID-level, emitted by the shell. Upon specific heat treatment, the ID is switched by irreversible quenching of the organic ID-level, revealing the inorganic ID-level. Furthermore, both ID-levels are read out ratiometrically using the same excitation wavelength for their detection. Based on the SPs’ toolbox-like manufacturing, the ID signals are adjustable to yield the demanded code variety on both ID-levels.<br
Keywords: coupling effects; ID taggants; luminescent nanoparticles; marker particles; rare-earth-doped particles; smart additives; supraparticles

Luminescent Supraparticles Based on CaF2-Nanoparticle Building Blocks as Code Objects with Unique IDs - Miller, Franziska; Wintzheimer, Susanne; Reuter, Tim; Groppe, Philipp; Prieschl, Johannes; Retter, Marion; Mandel, Karl (ACS Applied Nano Materials, 2020)
In the course of globalization, tracking of material supply chains and product protection against counterfeiting is a topic of increasing relevance. The labeling of raw materials or product components with encoded microstructures may therefore ensure their reliable and tamper-proof identification. In this work, luminescent lanthanide doped calcium fluoride nanoparticles with characteristic optical properties are assembled to micrometer-sized supraparticles via spray-drying. By wise selection of these nanoscale building blocks, it is possible to create spectrally encoded microparticles. Their code relies on the relative emission intensities of the different luminescent nanoparticles and their concentration ratios within the supraparticle. Due to this strategy, we offer a nanoscale modular approach for an easily adjustable and simple creation of ratiometric luminescence-encoded microparticles for the tamper-proof marking of objects.
CRIS-Team Scopus Importer:2020-04-02
Keywords: luminescent code; marker; nanoparticle assembly; rare earth doped nanoparticles; supraparticle

Rising Like a Phoenix from the Ashes: Fire-Proof Magnetically Retrievable Supraparticles with an Optical Fingerprint for Postmortem Identification of Products - Miller, Franziska; Wenderoth, Sarah; Wintzheimer, Susanne; Mandel, Karl (Advanced Optical Materials, 2022)
Counterfeit electronic products not only cause financial losses but also come with safety risks. The worst-case failure scenario certainly is a fire event. Since manufacturers are liable for damages and suffer image loss, fire-proof postmortem taggants are needed, enabling differentiation between originals and counterfeits even after a fire incident. This work presents such taggants: optomagnetic supraparticles (SPs), i.e., complex microscale particles composed of luminescent and magnetic nanoparticles (NPs) are generated. Their hybrid nature is pivotal, as magnetic separation can effectively remove the tags from light-absorbing fire debris, and a fire-proof identification (ID) fingerprint is based on ratiometric luminescence signals. To achieve thermally stable magnets, iron oxide (IO) NPs are wet-chemically coated with a SiO2-3-aminopropyltriethoxysilane (APTES) shell. Subsequently, these magnetic NPs are assembled with luminescent nanophosphors (lanthanide-doped calcium phosphate NPs with a SiO2-core) and SiO2-APTES spacer NPs by spray-drying to form hybrid SPs. The careful choice of type and ratios of the NPs and process parameters make it possible to achieve and precisely tune the desired functionality of the resulting fire-proof taggants. A proof-of-concept is demonstrated, in which the taggants are incorporated as additives into coatings and subjected to real fire simulations.
CRIS-Team Scopus Importer:2022-10-21
Keywords: fire-proof; ID tags; luminescent ID; magnetism at high temperature; oxidation-stable magnetism; postmortem ID; supraparticles

Supraparticles for Sustainability - Wintzheimer, Susanne; Reichstein, Jakob; Groppe, Philipp; Wolf, Andreas; Fett, Bastian; Zhou, Huanhuan; Pujales Paradela, Rosa; Miller, Franziska; Müssig, Stephan; Wenderoth, Sarah; Mandel, Karl (Advanced Functional Materials, 2021)
The indispensable transformation to a (more) sustainable human society on this planet heavily relies on innovative technologies and advanced materials. The merits of nanoparticles (NPs) in this context are demonstrated widely during the last decades. Yet, it is believed that the impact of particle-based nanomaterials to sustainability can be even further enhanced: taking NPs as building blocks enables the creation of more complex entities, so-called supraparticles (SPs). Due to their evolving phenomena coupling, emergence, and colocalization, SPs enable completely new material functionalities. These new functionalities in SPs can be utilized to render six fields, essential to human life as it is conceived, more sustainable. These fields, selected based on an entropy-rate-related definition of sustainability, are as follows: 1) purification technologies and 2) agricultural delivery systems secure humans “fundamental needs.” 3) Energy storage and conversion, as well as 4) catalysis enable the “basic comfort.” 5) Extending materials lifetime and 6) bringing materials back in use ensure sustaining “modern life comfort.” In this review article, a perspective is provided on why and how the properties of SPs, and not simply properties of individual NPs or conventional bulk materials, may grant attractive alternative pathways in these fields.
CRIS-Team Scopus Importer:2021-02-05
Keywords: nanomaterials; nanoparticles; supraparticles; sustainability

Supraparticles with silica protection for redispersible, calcined nanoparticles - Wintzheimer, Susanne; Miller, Franziska; Prieschl, Johannes; Retter, Marion; Mandel, Karl (Nanoscale Advances, 2019)
Calcination of nanoparticles is always accompanied by undesired sintering. A calcination route preventing hard-agglomeration to bulk lumps, which is transferable to almost any kind of metal oxide nanoparticle, is developed by surrounding targeted nanoparticles by silica nanoparticles within a nanostructured microparticle. After calcination, the desired nanoparticles are regained as a monodisperse sol via silica dissolution.
CRIS-Team Scopus Importer:2020-04-02